2014
DOI: 10.1068/i0597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surrounding Texture on the Pursuit-Pursuing Illusion

Abstract: The pursuit-pursuing illusion is a visual illusion where a circular object placed in the centre of a radial pattern consisting of thin sectors is seen to move in the pursuit eye movement direction. The present study investigates the role of the surrounding texture, replacing the sectors with random dots or stripes in an orientation that was orthogonal, parallel or oblique to the pursuit direction. The experiments demonstrate that the acquired illusory effect was large for the orthogonal stripes. However, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…It was also suggested that very small eye movements called microsaccades have an important role to play in the perception of shimmering [ 18 ]. Empirical evidence has been found to support this claim in the case of the Enigma illusion [ 19 ], as well as other illusions of motion based on geometric patterns [ 20 ][ 21 ][ 22 ].…”
Section: Introductionmentioning
confidence: 95%
“…It was also suggested that very small eye movements called microsaccades have an important role to play in the perception of shimmering [ 18 ]. Empirical evidence has been found to support this claim in the case of the Enigma illusion [ 19 ], as well as other illusions of motion based on geometric patterns [ 20 ][ 21 ][ 22 ].…”
Section: Introductionmentioning
confidence: 95%